Worship, Feasts and Ceremonies in the Early Jewish-Christian Church - Buchanan, George Wesley (New Testament studies, 1980)
Jewish-Christians readily interpreted the life, ministry and sacrificial death of Jesus in agreement with accepted Jewish concepts: the trinity, the apostolic christology of the Messiah, meritorious suffering in behalf of all Israel, reconciliation of Israel to God through the death of the Messiah, refusal to participate in active rebellion against Rome, and willingness to dispute with other religious sects about many points. The fall of Jerusalem taught them to adjust their worship practices according to Jewish traditions which deemed the temple unnecessary, but they continued to mourn for it and hope for its restoration. Daily and weekly private and congregational worship attempted to fulfil needs formerly met by the function of priests in the temple. Baptism became still more important than before, assuming more responsibility for cleansing from sins, but it did not make circumcision unnecessary. There continued to be scripture reading and exhortation in congregational worship services. Some of them observed the same calendar of feasts as the majority of Jews and also the Jewish Sabbath, but they adhered to the Lord's Day and perhaps some of them even concurred with Gentile-Christians in their Christian adjustments to the old agricultural calendar. Jewish-Christians of the second century were in closer agreement with the theology of the NT and Jews of their day than they would have been with Catholic Christians who lived a few centuries later.